Functional-semantic features of the actual participles of the present and past time in the Tale of Bygone Years - Matsiunova, Antonina A. (Journal of the Belarusian State University. Philology, 2019)
The article is written in the vein of the historical functional semantics. The article describes semantic features of the ancient Russian participles. Aim of the article is to establish semantic and functional differences between participles, which are used in The tale of bygone years. The article defines four groups of words: participles, which expressed the temporary adjective actional attribute; participles, which expressed a permanent adjective actional attribute; substantivized participial words; participles which called secondary actional attribute. It is proved that the semantic differences between Old Russian participles should be taken into account, when the speakers of the modern Russian language read Old Russian text, for the adequate understanding of the meaning, which is invested by the medieval author in the text.